Tren Penelitian Etika dan Hak Cipta dalam Perpustakaan: Analisis Bibliometrik - Arya Wijaya Pramodha Wardhana; Ike Iswary Lawanda (Media Pustakawan, 2024)
Ethics and copyright are significant topics within the context of libraries, as libraries play a crucial role as information regulators. This bibliometric study aims to identify research trends related to ethics and copyright in the library context from 2014 to 2024. Data were obtained from the Scopus database using the query term: "((TITLE-ABS-KEY (copyright AND compliance AND in AND libraries) OR TITLE-ABS-KEY (ethical considerations AND for AND librarians) OR TITLE-ABS-KEY (access to information AND copyright AND issues))", resulting in 195 documents analyzed using bibliometric tools like Scopus, Vosviewer, and R (Bibliometrix). The research findings indicate that discussions on ethics and copyright in libraries are prevalent in advanced countries with large populations like United States, India, Canada, and China. It is also observed that the number of publications on this topic has declined since 2014 through 2024. Key journals addressing this topic include Library and Philosophy Practice, PLOS One, and the International Journal of Communication System. Dominant keywords in this study encompass human aspects (human, male, female) and regulatory aspects (article, and copyright). Network mapping results show that keywords are divided into 4 main clusters: information processing cluster, academic library & information access cluster, control & copyright cluster, and management cluster